MLL4 regulates postnatal palate growth and midpalatal suture development - Lee, Jung-Mi; Jung, Hunmin; Pasqua, Bruno de Paula Machado; Park, Yungki; Tang, Qinghuang; Jeon, Shin; Lee, Soo-Kyung; Lee, Jae W.; Kwon, Hyuk-Jae Edward (Frontiers in Cell and Developmental Biology, 2025)
MLL4, also known as KMT2D, is a histone methyltransferase that acts as an important epigenetic regulator in various organogenesis programs. Mutations in the MLL4 gene are the major cause of Kabuki syndrome, a human developmental disorder that involves craniofacial birth defects, including anomalies in the palate. This study aimed to investigate the role of MLL4 and the underlying mechanisms in the development and growth of the palate. We generated a novel conditional knockout (cKO) mouse model with tissue-specific deletion of Mll4 in the palatal mesenchyme. Using micro-computed tomography (CT), histological analysis, cell mechanism assays, and gene expression profiling, we examined palate development and growth in the Mll4-cKO mice. Gross craniofacial examination at adult stages revealed mild midfacial hypoplasia and midline defects of the palate in Mll4-cKO mice, including a widened midpalatal suture and disrupted midline rugae pattern. Micro-CT-based time-course skeletal analysis during postnatal palatogenesis through adulthood demonstrated a transverse growth deficit in overall palate width in Mll4-cKO mice. Whole-mount and histological staining at perinatal stages identified that the midline defects in the Mll4-cKO mice emerged as early as 1 day prior to birth, presenting as a widened midpalatal suture, accompanied by increased cell apoptosis in the suture mesenchyme. Genome-wide mRNA expression analysis of the midpalatal suture tissue revealed that MLL4 is essential for the timely expression of major cartilage development genes, such as Col2a1 and Acan, at birth. Immunofluorescence staining for osteochondral differentiation markers demonstrated a marked decrease in the chondrogenic marker COL2A1, while the expression of the osteogenic marker RUNX2 remained unchanged, in the Mll4-cKO midpalatal suture. Additionally, SOX9, a master regulator of chondrogenesis, exhibited a significant decrease in protein expression. Indeed, time-course histological analysis during postnatal palate growth revealed retardation in the development of the suture cartilage in Mll4-cKO mice. Taken together, our results demonstrate that MLL4 is essential for orchestrating key cellular and molecular events that ensure proper midpalatal suture development and palate growth.